Hysteroscopic fetoscopy: A role as virtuopsy for parents who refuse full autopsy? A case of facial clefting, proboscis, and limb deformities - Gabriele Tonni; Enrico Periti; Lucia Rosignoli (Elsevier, 2015)
Objective: To describe the value of hysteroscopic fetoscopy (virtuopsy) at the time of uterine suction in a case of early diagnosis of congenital anomalies in parents refusing conventional full autopsy examination. Case report: First trimester ultrasound diagnosis of proboscis, median cleft lip and palate and limb deformities. Chorionic villus sampling demonstrated normal karyotype. Parents refused medical induction of termination of pregnancy with subsequent conventional autopsy. At this stage, hysteroscopic fetoscopy was consented and carried out under local anesthesia prior to uterine evacuation. Conclusion: Hysteroscopic fetoscopy (virtuopsy) proved to be a valuable complementary diagnostic investigation and enhanced the parental bonding process concerning the fetal phenotype. Notwithstanding, the woman declared an acceptable compliance during the procedure. In selected cases, virtuopsy may be a valid option in confirming early prenatal ultrasound diagnosis in parents refusing conventional autopsy or when full postmortem examination may not be clinically indicated or warranted.